2017
DOI: 10.1080/23328940.2017.1328304
|View full text |Cite
|
Sign up to set email alerts
|

The effect of environmental temperature on exercise-dependent release of brain-derived neurotrophic factor

Abstract: Brain-derived neurotrophic factor (BDNF) is a biomarker of cognitive function that is released into the blood stream following exercise, and cognitive function is impaired by environmental temperatures that are hot and cold. Purpose: To evaluate the exercise-dependent release of BDNF in different environmental temperatures. Methods: Recreationally trained males each completed three trials consisting of cycling for 1 h at 60% W max at three different temperatures: 33 C (hot), 7 C (cold), and 20 C (moderate room… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…It should be noted that the acute BDNF response was modest (~20% increase) compared to several other exercise studies. For instance, 1 h of cycling at 55-60% peak oxygen uptake results in a ~50% increase in serum BDNF concentration 30,31) . In contrast, the BDNF response in the present study is more in line with shorter duration (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the acute BDNF response was modest (~20% increase) compared to several other exercise studies. For instance, 1 h of cycling at 55-60% peak oxygen uptake results in a ~50% increase in serum BDNF concentration 30,31) . In contrast, the BDNF response in the present study is more in line with shorter duration (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Snipe et al (Snipe et al 2016;Snipe et al 2018a) have reported a dose response in post-exercise intestinal damage, as measured by I-FABP, with increasing environmental temperature from 22°C to 30°C and 22°C to 35°C. While the damage may in part be attributed to increasing ambient temperature, participants were running at the same absolute treadmill speed during each trial and as such exercise intensity may have differed in the hot versus temperate conditions given the possible increased physiological strain and metabolic cost of exercising in the heat (No and Kwak 2016;Collins et al 2017). In the presence of cardiovascular drift when exercising in the heat at a set workload, heart rate remains a reliable indicator of relative exercise intensity (Wingo 2015) and Snipe et al (Snipe et al 2018a;Snipe et al 2018b) reported significantly higher heart rates (and ratings of perceived exertion) when exercising at the same absolute intensity in 30°C and 35°C compared to 22°C, indicating greater physiological strain when exercising it the heat .…”
Section: Page 3 Of 26mentioning
confidence: 99%